Fabrication and mechanical behaviors of iron–nickel foam reinforced magnetorheological elastomer. (22nd October 2019) - Li, Yaping; Qi, Song; Fu, Jie; Gan, Ruyi; Yu, Miao
Abstract: Magnetorheological elastomers (MREs) have excellent magnetic-control mechanical properties, which ensures its great engineering application value in the field of vibration control. In this paper, the iron–nickel foam (INF) reinforced MREs with excellent magnetorheological (MR) properties were developed. The soft magnetic properties and three-dimensional (3D) foam structure of INF ensure an effective enhancement on the magnetic-control mechanical properties of MRE. The static and dynamic mechanical properties of the MRE were tested based on a parallel plate rheometer. Among them, static compression tests were carried out to study the static mechanical properties of MREs. The test results showed that INF reinforced MREs have excellent magneto-induced compression modulus. The effects of magnetic field, shear strain, and frequency on the dynamic mechanical properties of MREs have studied by the dynamic oscillatory shear tests. The test results revealed that the MRE has excellent MR properties under small strain. In addition, several successive tests were conducted to evaluate the response behavior under transient magnetic field and hysteresis properties of MREs under periodic magnetic field, and no obvious hysteresis in the repeated test curves have been observed. The INF reinforced MRE studied in this paper has potential application prospects in the field of micro-vibration control.